Calf feeding and management: The effect of genotype (Bos taurus x Bos indicus) level of milk feeding and type of housing on the post-weaning growth performance of crossbred calves upto one year of age - Osuji, P.O.; Yimegnuhal, A.; Umunna, N.N.; Tegegne, Azage (Ethiopian Society of Animal Production, 2000)
The effect. of genotype (50% 75% and 87.50, levels of milk (2 and 3 1/day) and types of housing (Barn and Hutch) were examined using 38 Boran x Friesians crossbred calves (Bos Taurus x Bos indicus). Calves were offered supplement diet (180 g/kg CP and 100g/kg roughage) and were weaned until their supplement intake reached 450 g/day for two consecutive days. Then after they were moved to another pen and provided with hay ad libiitum and concentrate equivalent to 1.5% of their body weight for three months. Subsequently they were moved to feedlot and were provided teff straw, ad libiitum and, supplemented with one kg/day concentrate diet (wheat middling) until one year of age. Average daily gain (ADG) of 50%, 75% and 87.5% calves from weaning to one year of age was 300, 242, 253 g/day (SE (+ or -) 15.70), respectively and was not different significantly (p>0.05). Mean final body weight of calves with 50% exotic blood level was superior by 16.2% and 10.3% than those with 75% and 87.5% exotic blood levels, respectively, but the differences were not significant (p<0.05). Body weight of calves reared at one year of age on 2 1 and 3 1 of milk was 115 and 124, kg (SE (+ or -) 4.38), respectively and did not differ significantly (p>0.05). There was no interaction (p>0.05) among main effects.